Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.20517/2394-5079.2016.28
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating normalization approaches for the better identification of aberrant microRNAs associated with hepatocellular carcinoma

Abstract: Aim Dysregulated microRNAs (miRNAs) have been identified in hepatocellular carcinoma (HCC), but only a small proportion have been confirmed. An appropriate normalizer is crucial to determining the accuracy and reliability of data from miRNA studies. Methods Different normalization strategies were used to validate genome-wide miRNA profiles in HCC tumor and non-tumor tissues, and to determine the consistency and discrepancy of data on dysregulated miRNAs. Results Two sets of stable miRNAs (miR-30c/miR-30b a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…A recent study of our group showed how the miRNA profile of HCCs changed using a pool of cirrhotic tissues or a pool of healthy livers as non-tumor controls[ 121 ]. Other authors suggested to employ stable miRNAs as controls for the study of the expression of other miRNAs[ 122 ]. In the light of the available data, it would be useful to elaborate, based on the most representative miRNA in in vivo model ( e.g ., rat, mouse), to better understand the possible role of these molecules as theragnostic markers in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of our group showed how the miRNA profile of HCCs changed using a pool of cirrhotic tissues or a pool of healthy livers as non-tumor controls[ 121 ]. Other authors suggested to employ stable miRNAs as controls for the study of the expression of other miRNAs[ 122 ]. In the light of the available data, it would be useful to elaborate, based on the most representative miRNA in in vivo model ( e.g ., rat, mouse), to better understand the possible role of these molecules as theragnostic markers in HCC.…”
Section: Discussionmentioning
confidence: 99%
“… 13 , 14 , 16 , 17 It was reported that aberrant expression of miR-30c was a potential early diagnostic marker in HCC. 18 , 24 Meanwhile, miR-30c downregulation was associated with HCV core protein-induced EMT in HCC cells. 25 In our study, we demonstrated that the expression of miR-30c-5p is downregulated in HCC, and reduced miR-30c-5p expression predicts poor prognosis in HCC patients.…”
Section: Discussionmentioning
confidence: 97%
“…Dre-miR-30c-5p is known as a key player in pronephric development in Xenopus laevis and Danio rerio, where it shows a pronephros specific expression within the first days of development 34,35 . It has also been used as an endogenous reference gene before 36 . Unfortunately, there were significant dre-miR-30c-5p expression differences between different developmental stages, meaning that it had to be rejected as a suitable normalizer for that kind of experimental setups.…”
Section: Discussionmentioning
confidence: 99%